The Application of Prenatal Yoga as Complementary Care to Improve Reproductive Health and the Well-Being of Pregnant Women - Afrilia, Eka Mardiana; Martini, Titin; Musa, Siti Mardhatillah; Lestari, Murni (MSJ : Majority Science Journal, 2025)
This study explores the application of prenatal yoga as a complementary care approach to enhance reproductive health and overall well-being among pregnant women. Pregnancy involves complex physiological and psychological changes that often lead to discomfort, stress, anxiety, and reduced physical mobility. While conventional medical care remains essential for monitoring maternal and fetal health, it often does not fully address the emotional, psychological, and musculoskeletal challenges experienced during pregnancy. This study employs a qualitative descriptive literature review, synthesizing findings from international and national journals, WHO, ACOG, UNICEF, and other clinical guidelines published between 2018 and 2025. The results reveal that prenatal yoga contributes to improved physical comfort, reduced back and pelvic pain, regulated breathing, and enhanced autonomic balance through parasympathetic activation. Psychologically, prenatal yoga reduces stress and anxiety, improves sleep quality, and strengthens emotional bonding between mother and fetus. Furthermore, the integration of prenatal yoga with conventional antenatal care enhances maternal preparedness for childbirth and supports postpartum recovery. However, challenges remain, particularly regarding limited availability of certified prenatal yoga instructors and insufficient awareness among healthcare providers in Indonesia. Overall, prenatal yoga proves to be a safe, effective, and holistic complementary intervention that supports maternal health and aligns with modern reproductive care standards. Its integration into primary healthcare services may significantly improve maternal well-being and promote healthier pregnancy outcomes.